Damaging Effect of Static and Moving Armoured Vehicles with Rubber Tires on Flexible Pavement - Sultan, Saud A. (Nahrain University College of Engineering Journal, 2011)
The damaging effect of military armoured vehicles with rubber tires on flexible pavements was studied. Two types of military armoured vehicles with rubber tires were considered, namely CM32 four-axle and CM32 triple-axle. A measure of the damaging effect of military armoured vehicles with rubber tires loads was achieved by correlating their equivalent loads with the AASHTO equivalency factors. The equivalent load was developed on the basis of mechanistic - empiricalapproach. It was found that the damaging effect of the studied loads of CM32 four-axle military armoured vehicle with rubber tires is 0.262-2.853 times the damaging effect of the standard 18 kips (80 kN) axle load depending on the thickness of asphalt layer. It was found that the damaging effect of the studied loads of CM32 triple-axle military armoured vehicle with rubber tires is 0.933-4.880 times the damaging effect of the standard 18 kips (80 kN) axle load depending on the thickness of asphalt layer. It was found that the damaging effect of the braking forces of CM32 four-axle military armoured vehicle with rubber tires is 40 times the damaging effect of the CM32 four-axle military armoured vehicle weight only. It was found that the damaging effect of the braking forces of CM32triple-axle military armoured vehicle with rubber tires is 5 times the damaging effect of the CM32 triple-axle military armoured vehicle weight only.